Survei Motivasi Mengikuti Pembelajaran Pendidikan Jasmani Aktivitas Permainan Tradisional (Tunagrahita) (Department of Physical Education, Sport, Health and Recreation, 2017)
The existing problems in this research is how the level of motivation to follow the teaching of physical education activities of traditional games in Class V section C (retarded) in SLB N Tegal. So the purpose of this research is to determine how much motivation particaipated in physical education activity of traditional games for 5th grade section c (mentally disabled) students. Approach in this research is qualitative approach used descriptive method. Methods of this research used observation, interviews, and documentation. Data analysis in this research used data collection, data reduction, data display, and conclusion drawing. The result showed that motivation students 5th grade section C (mentally disabled) included in medium category were learning education at the physical activity traditional games. Included in medium category could be seen from characteristic behavior of student shown at learning activity of tradisional games. There was persevering, tenacity, pleasure, and interest that was shown the motivation of student included medium category. The conclusions of this research are: motivation in class V section C (retarded) in SLB N Tegal included in the medium category during the learning of physical education activity traditional games.